2014
DOI: 10.4067/s0718-95162014005000008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of soil properties of Nothofagus spp. forest with and without scarification in the Andean region of Southern Chile

Abstract: Soil scarification has been used as a silvicultural method to eliminate competition in tree regeneration, but it modifies soil characteristics. In order to evaluate soil changes due to silvicultural management, we characterized a volcanic soil subjected to a mechanized scarification in a Nothofagus spp. forest in the Andean region of southern Chile (39° 54' S, 71° 56' W; 970 m asl). Scarification removed between 20 and 40 cm of topsoil in forest gaps. Two scarified areas were selected in different periods and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 19 publications
3
14
0
2
Order By: Relevance
“…Our study showed that topsoil removal was a successful treatment in high‐graded Nothofagus forests in the Andes of south‐central Chile, as it reduced the abundance of C. culeou and at the same time encourages the regeneration of desirable LLES tree species. This supports findings in a number of forest biomes that this ground disturbance can be an effective practice for altering understorey vegetation to encourage tree regeneration (Löf et al., ; Örlander et al., ; Reyes et al., ; Yoshida et al., ). Research has shown that a variety of environmental conditions can be responsible for this effect, including the amount of soil exposure needed to provide safe sites (Cornett, Reich, Puettmann, & Frelich, ), degree of soil compaction (Ampoorter, De Frenne, Hermy, & Verheyen, ; Soto, Donoso & Puettmann, 2014) and soil fertility (Ampoorter et al., ; Reyes et al., ).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Our study showed that topsoil removal was a successful treatment in high‐graded Nothofagus forests in the Andes of south‐central Chile, as it reduced the abundance of C. culeou and at the same time encourages the regeneration of desirable LLES tree species. This supports findings in a number of forest biomes that this ground disturbance can be an effective practice for altering understorey vegetation to encourage tree regeneration (Löf et al., ; Örlander et al., ; Reyes et al., ; Yoshida et al., ). Research has shown that a variety of environmental conditions can be responsible for this effect, including the amount of soil exposure needed to provide safe sites (Cornett, Reich, Puettmann, & Frelich, ), degree of soil compaction (Ampoorter, De Frenne, Hermy, & Verheyen, ; Soto, Donoso & Puettmann, 2014) and soil fertility (Ampoorter et al., ; Reyes et al., ).…”
Section: Discussionsupporting
confidence: 85%
“…Thus, a close examination of soil conditions, specifically nutrient and soil water conditions, will provide insights into the likelihood of success when applying topsoil removal as a restoration treatments. Earlier work (Reyes et al., ) also pointed out that soil structure, specifically the potential for soil compaction, needs to be considered when such restoration treatments are applied across a broader landscape.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations